2016
DOI: 10.1016/j.xphs.2016.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Improving Biopharmaceutical Properties of Vinpocetine Through Cocrystallization

Abstract: Vinpocetine is a poorly water soluble weakly basic drug (pK = 7.1) used for the treatment of several cerebrovascular and cognitive disorders. Because existing formulations exhibit poor bioavailability and scarce absorption, a dosage form with improved pharmacokinetic properties is highly desirable. Cocrystallization represents a promising approach to generate diverse novel crystal forms and to improve the aqueous solubility and in turn the oral bioavailability. In this article, a novel ionic cocrystal of vinpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…In this context, we have recently shown that the formation of halogen-bonded API-CCF cocrystals is a further opportunity offered by this interaction in biopharmacology [29,30]. The relevance of this opportunity is confirmed by the numerous halogen-bonded cocrystals of pharmaceutical interest reported after our papers [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 55%
“…In this context, we have recently shown that the formation of halogen-bonded API-CCF cocrystals is a further opportunity offered by this interaction in biopharmacology [29,30]. The relevance of this opportunity is confirmed by the numerous halogen-bonded cocrystals of pharmaceutical interest reported after our papers [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 55%
“…As another example of studies on the bioavailability of cocrystals in human, Golob and coworkers 128 reported vinpocetine-boric acid ionic cocrystal which remarkably improved in vitro powder dissolution in comparison to pure vinpocetine. The authors conducted the in vivo oral absorption studies in healthy human subjects.…”
Section: Pharmacokinetic Studies In Humanmentioning
confidence: 99%
“…Therefore, it is important to establish effective methods for enhancing the dissolution and bioavailability of NOMAC. It is agreed that co-crystals form a vital part of the solidstate toolbox for improving the properties of older medicines [7][8][9][10]. To date, researchers have obtained many co-crystals of the steroids to improve their dissolution compared with the pure counterpart [11,12].…”
Section: Commentmentioning
confidence: 99%